Aplicação de atividades de modelagem matemática na construção de sequências didáticas contextualizadas na astronomia - Carvalho, Claudiana de Souza Santos (2018)
This dissertation describes a teaching experience that used Mathematical Modeling activities in the construction of didactic sequences contextualized in Astronomy and implemented in classes of the 9th grade of Elementary School II of a public school in the state of Bahia. The main objective was to take to the classroom a meaningful learning proposal and promote, in an interdisciplinary way, the teaching of Astronomy and Mathematics, as it guides the National Curricular Parameters (PCN) (BRASIL, 1997). It was also sought to investigate, through the application of this methodology, how the contextualized use of knowledge of some concepts of Astronomy, oriented by PCN, in a learning environment using Mathematical Modeling, can provide students with motivation to study science and consolidate knowledge of Astronomy and Mathematics. In this sense, it was sought that the students had the perception of astronomical phenomena and related them to the daily life. In order to reach the objective, sequenced activities were proposed to explain: a) the emergence of day and night; b) visualization of the duration of the day and night part of the day as a function of latitude; c) demonstration on how the seasons of the year occur; d) occurrence of lunar eclipses and Moon phases; and e) the Solar System. The activities followed a sequenced pattern where the initial part was always the contact with a topic of Astronomy, studied, experienced or observed and then the mathematical understanding of the phenomenon studied. Finally, three didactic sequences were obtained as an educational product resulting from this interdisciplinary teaching-learning process of Astronomy and Mathematics.